As possíveis relações entre as competências digitais docentes e a qualidade da educação na rede pública do município de Passo Fundo no período de 2022 a 2024 - Costa, Flaiane Rodrigues (2024)
This study aims to map the digital skills of teachers in the municipal education network of Passo Fundo/RS, with the aim of identifying possible relationships between such skills and the quality of education in the municipality. In view of the exposition, the question that guides this study is the following: What are the relationships between the digital skills of teachers and the quality of education in the Passo Fundo municipal education network in the period 2022/2024? The objectives of this research are outlined as follows: to investigate the effects of a continuing training process on expanding teachers' digital skills and competencies, as well as its impacts on the quality of education; analyze public policies that encourage the use of technologies in the educational context; interpret education quality indicators and, based on them, infer the concept of quality education; and systematize large-scale assessment and diagnostic instruments, with the aim of measuring the quality of education in the municipality of Passo Fundo/RS. To address the research question and achieve the outlined objectives, we defined the methodological approach, which begins with a review of research already conducted on this topic. Subsequently, we turn to the theoretical basis that underpins the research. Regarding empirical research, we used the EDUTEC Guide script, a tool adapted from the original script, preserving the integrity of the real data. The questionnaire developed aims to diagnose the level of adoption of educational technology by teachers and managers. This data must be compared with the municipality's diagnostic assessment in the years 2021 and 2022, considering investments in infrastructure and teacher training, with the aim of finding out whether there is a correlation between teachers' digital skills and the quality of education in the municipal network. teaching center in Passo Fundo - RS. Analyzes carried out using primary and secondary data indicate that digital technologies do not compromise the quality of education in the Passo Fundo municipal education network. On the contrary, these technologies enhance teaching practice, making classes more dynamic and attractive for students.